Wybrane zagadnienia prawne pomocy de minimis w rolnictwie - SUCHOŃ, ANETA (Wydawnictwo Naukowe UAM, 2011)
The de minimis assistance in agriculture is a relatively new issue in the Polish agricul-tural law. It is connected with the introduction of EU principles of financial support for this sector of the Polish economy. The aim of these considerations was to present an attempt at a possibly comprehensive approach to problems connected with de minimis assistance in agriculture and to clarify doubts found in practice. In conclusion the author states among other things that EU regulations very generally define de minimis assistance, which sometimes causes problems with its interpretation, but creates a chance for the prompt introduction of new forms of assistance by individual member countries, taking into consideration current needs of agricultural producers. Certain legal acts expressis verbis define a given assistance as de minimis, while other disregard this issue. In practice many problems are caused by the individual premises for the granting of a specific type of this assistance. These considerations are concluded with an attempt at a classification of de minimis assistance in agriculture.

Gli aiuti de minimis in agricoltura fanno parte delle questioni relativamente nuove del diritto agrario polacco. Essi sono legati all’introduzione delle regole europee di sostegno finanziario a questo settore dell’economia nel nostro paese. Lo scopo delle considerazioni è un tentativo di proporre un inquadramento abbastanza olistico delle più importanti questioni relative agli aiuti de minimis in agricoltura e di risolvere delle questioni dubbiose verificatesi in pratica. In conclusione, l’Autrice afferma, tra l’altro, che le norme dell’Unione determinano gli aiuti de minimis in maniera molto generale, il che porta a volte a delle difficoltà di inter-pretazione, ma crea anche l’opportunità di una rapida introduzione di nuove forme di aiuto da parte degli Stati membri, tenendo conto delle attuali esigenze dei produttori agricoli. Alcuni atti giuridici definiscono un dato aiuto in termini di aiuto de minimis expressis verbis, mentre altre ignorano il problema. Numerose difficoltà pratiche derivano dalle condizioni dettagliate relative alla concessione del concreto tipo dell’aiuto in questione. Le considerazioni terminano con una proposta di classificazione degli aiuti de minimis in agricoltura.